PENGGUNAAN SECOND LANGUAGE PADA KEMAMPUAN BAHASA EKSPRESIF ANAK USIA 3-5 TAHUN DI SUNNY GLOW MONTESSORI PLAYSCHOOL MANYAR - Catharine Laboure Nimas Ayu Anindita; Rofik Jalal Rosyanafi; Anisa Yunita (Universitas Narotama, 2022)
During the early childhood education level (0-6 years) English is used as a semi-introduction to everyday language to introduce basic things to children such as colors, numbers, shape, and other daily habits such as shaking hands and washing hands. This is the purpose of providing English education as early as possible. The impact that arises because learning a second language is given from a young age, among others, makes language acquisition in children increase. LAD (Language Acquisition Device) or the ability to acquire language is an innate ability possessed by every human being or as a language device acquired by children from birth will become more active so as to improve children''s language acquisition.